Learning from Educational Impediments: Insights for Nigeria from the Tigray Conflict - Ezugwu, Olileanya Amuche; Udom, Adaeze; Kehinde, Tola Benjamin (Journal of Central and Eastern European African Studies, 2024)
Education serves as a crucial foundation for the advancement and prosperity of any nation, shaping individuals, empowering communities, and fostering economic growth. Nevertheless, educational systems are vulnerable to disruption caused by conflicts and violence, resulting in significant consequences for students, teachers, and educational institutions. This study examines the educational impediments faced in Tigray from the Ethiopian-Tigray conflict, the potential lessons that Nigeria can learn and strategies Nigeria should implement to mitigate these challenges. The study employed a qualitative method using case study research design. Purposive sampling technique was used to select twelve interview participants for the primary data, while secondary data were collected from scholarly publications, journals, articles, and online materials. The findings revealed common obstacles encountered by Ethiopia's educational sector, including disrupted access to schooling, displacement of students and teachers, infrastructure damage, loss of learning resources, and psychological trauma among students. These challenges significantly hindered the provision of quality education and impeded progress toward achieving the Sustainable Development Goals (SDGs) in education. This study concludes that education plays a vital role in Nigeria's economic growth and political stability, and by drawing upon Ethiopia's experiences recommends Nigeria to enhance its resilience and preparedness in similar crises, such as strengthening emergency education response mechanisms, investing in inclusive and community-driven education, bolstering infrastructure resilience, and prioritising psychosocial support for affected students among others.